2018
DOI: 10.1186/s12913-018-2929-9
|View full text |Cite
|
Sign up to set email alerts
|

Using PROMIS for measuring recovery after abdominal surgery: a pilot study

Abstract: BackgroundTo assess the construct validity and responsiveness of the PROMIS Physical Function v1.2 short form 8b (PROMIS-PF), and the PROMIS Ability to Participate in Social Roles and Activities v2.0 short form 8a (PROMIS-APS) in postoperative recovery.MethodsAn observational pilot study was conducted in which 30 patients participated, undergoing various forms of abdominal surgery. Patients completed the PROMIS-PF and PROMIS-APS, the Short Form 36 Health Survey (SF-36) and the World Health Organization Disabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…The hypothesis for the former correlation was based on a Dutch study among 30 abdominal surgery patients that reported a correlation of 0.72 between the SF‐36 subscale Role limitations caused by physical health problems and the eight‐item PROMIS Ability to Participate in Social Roles and Activities short form. 40 Though the correlation we report is below the 0.70 threshold, it is of the same order of magnitude and the difference may be due to random variation or to differences in the underlying constructs being measured.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…The hypothesis for the former correlation was based on a Dutch study among 30 abdominal surgery patients that reported a correlation of 0.72 between the SF‐36 subscale Role limitations caused by physical health problems and the eight‐item PROMIS Ability to Participate in Social Roles and Activities short form. 40 Though the correlation we report is below the 0.70 threshold, it is of the same order of magnitude and the difference may be due to random variation or to differences in the underlying constructs being measured.…”
Section: Discussionmentioning
confidence: 54%
“… 37 Convergent validity was assessed with Pearson's correlations. We expected strong correlations ( r ≥ .70 or r ≥ −.70) between similar subscales of PROMIS‐29 with RAND‐36 subscales and HAL domains, based on published literature 38 , 39 , 40 and expert judgment (authors E.v.B. and S.G.), as shown in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…Construct validity was studied by testing hypotheses regarding the relationship of PROMIS items banks with the legacy instruments (convergent validity) as well as regarding expected differences between subgroups (known‐group validity). Hypotheses were defined a priori based on the literature 13 , 14 , 31 , 36 , 37 , 38 , 39 and expert opinion (KF, MT, MP, MC, SG, MHC, MK) and are presented in Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
“…Research into the feasibility and usefulness of PROMIS in many specialties has consistently found it to be of benefit when utilized appropriately. 10,11 The utility of PROMIS has not been documented in the eye care setting. Prior studies have described several vision-oriented questionnaires, some of which have been shown to reliably correlate vision-specific medical diagnoses with visual function and detriments to vision-related quality of life; 4,[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] however, few studies have used nonvision-specific PROs in the eye care setting, [28][29][30][31] and the use of general PROs to identify individuals at greater risk for comorbid medical or psychosocial life disturbances due to visual impairment, or of visual impairment due to other medical or psychosocial factors, remains less certain.…”
Section: Introductionmentioning
confidence: 99%